Causes and consequences of personalities in microtine rodents - Lantová, Petra (Jihočeská univerzita, 2011)
This thesis focuses on individually specific differences in behavioural strategies, personalities, with two microtine rodents (Microtus arvalis and M. oeconomus) as study species. The work evaluates methodology necessary to reveal and measure consistent individual differences in behaviour, identifies possible proximate and ultimate mechanisms behind the existence of individual behavioural variability, and describes some ecological, evolutionary and behavioural consequences of personalities.
Causes and consequences of personalities in microtine rodents
Keywords: animal personality; Microtus; rodents; open field test; animal personality; Microtus; rodents; open field test